The effect of cellulase-hydrolyzed chitosan on the degree of deacetylation, solubility and viscosity of chitosan oligosaccharides - Nurhayati, Yusof; Mohamad Azman, Ezzat; Abd. Ghani, Asmaliza; Yusof, Norzaida; Tang, John Yew Huat (Innovative Scientific Information and Services Network, 2021)
Chitosan is a source of potential bioactive material with many uses in the food, health and agricultural sectors. However, the limitation to utilize the chitosan in biological applications, comprising poor solubility under physiological conditions. In order to overcome the limitations, chitosan is being partially hydrolysed to produce chitosan oligosaccharides (COS). The objective of this research was to determine the degree of deacetylation (DDA), solubility and viscosity of the chitosan and COS. In this study, chitosan was hydrolysed by the cellulase from Trichoderma reesei to produce COS. The DDA of chitosan and COS were determined by linear potentiometric titration. The physical characteristics including solubility and viscosity were assessed. The COS was characterized by the degree of polymerization (DP) and FTIR spectroscopy by examining the structural changes before and after the degradation of chitosan. COS showed a higher DDA (99.69 % ± 0.28) compared to chitosan obtained from Sigma Aldrich (77.54 % ±0.28). This enzymatic product, COS also showed high solubility in aqueous and acidic solutions as compared to the chitosan sample. The product of hydrolysis of chitosan mainly composed of COS, with the DP 1-2. The IR spectrum showed that there was no significant change of chitosan before and after the enzymatic hydrolysis confirming the conservation of the chemical phase of the chitosan. In conclusion, COS preparation using cellulase, a low-cost commercial enzyme could open a wide range of new potential applications to improve the quality of many foods.